Regional Population-Employment Dynamics across Different Sectors of the Economy - Thomas de Graaff; Frank G. van Oort; Raymond J.G.M. Florax (Tinbergen Institute, 2011)
An important subset of the literature on agglomeration externalities hypothesizes thatintrasectoral and intersectoral relations are endogenously determined in models of localand regional economic growth. Remarkably, structural adjustment models describing thespatio-temporal dynamics of population and employment levels or growth traditionally donot include intersectoral economic dynamics. This paper argues and shows that allowingfor economic linkages across sectors in these models adds considerable value, especially inforecasting. An econometric model of population-employment dynamics in which sectoralvariations in economic development are explicitly taken into account is applied to a largeurban planning policy proposal in The Netherlands. The empirical analyses suggest thatpopulation dynamics are largely exogenous, population changes drive employment in particular in the industry and retail sectors, and employment in all sectors depends strongly onintersectoral dynamics. Intersectoral dynamics appear as important drivers of regional sectoral employment changes; they are even more important than population changes, and theireffect shows up clearly even within the Dutch institutional context where strict regulatoryhousing and planning restrictions are enforced.
urn:NBN:nl:ui:31-1871/38542
Keywords: C31; R11; R41; R58; 330; Spatial planning; population-employment dynamics; sectoral decomposition; agglomeration externalities; spatial econometrics; Regionale Entwicklung; Regionaler Arbeitsmarkt; Regionale Wirtschaftsstruktur; Agglomerationseffekt; Regionale Bevölkerungsentwicklung; Prognoseverfahren; Niederlande